2017
DOI: 10.1038/s41598-017-03782-x
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin beta-4 regulates activation of hepatic stellate cells via hedgehog signaling

Abstract: The molecular mechanisms of thymosin beta-4 (TB4) involved in regulating hepatic stellate cell (HSC) functions remain unclear. Therefore, we hypothesize that TB4 influences HSC activation through hedgehog (Hh) pathway. HSC functions declined in a TB4 siRNA-treated LX-2. TB4 suppression downregulated both integrin linked kinase (ILK), an activator of smoothened, and phosphorylated glycogen synthase kinase 3 beta (pGSK-3B), an inactive form of GSK-3B degrading glioblastoma 2 (GLI2), followed by the decreased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…Surprisingly, there is a decrease in PPAR γ expression in the T β 4-treated control. However, this result supports other reports which show that without liver injury, silencing T β 4 results in an increase in PPAR γ expression, and our results show that without liver injury, exogenously administering T β 4 results in a decrease in PPAR γ expression [ 59 , 62 ]. T β 4 also reduced the extent of fibrosis as measured by the percentage of collagen fibers and the amount of hydroxyproline in the liver tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, there is a decrease in PPAR γ expression in the T β 4-treated control. However, this result supports other reports which show that without liver injury, silencing T β 4 results in an increase in PPAR γ expression, and our results show that without liver injury, exogenously administering T β 4 results in a decrease in PPAR γ expression [ 59 , 62 ]. T β 4 also reduced the extent of fibrosis as measured by the percentage of collagen fibers and the amount of hydroxyproline in the liver tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Hong et al demonstrated that T β 4 inhibited HSC activation by suppressing Notch signaling, thus attenuating liver fibrosis [ 61 ]. Others have shown that T β 4 regulates HSC activation via hedgehog signaling [ 62 ]. Additionally, depletion of T β 4 has shown to promote the proliferation, migration, and activation of HSC [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reyes-Gordillo et al 21 reported that administration of Tβ 4 prevented necrosis, inflammatory infiltration and up-regulation of α1 (and 2) collagen, α-smooth muscle actin (α-SMA), platelet-derived growth factor (PDGF)-β receptor, and fibronectin mRNA expression in a rat model of acute CCl 4 intoxication. A study by Kim et al 22 showed that exogenous Tβ 4 administration significantly attenuated CCl 4 -induced liver fibrosis in rats. This protective effect was attributed to the alleviation of oxidative stress and inflammation by Tβ4.…”
mentioning
confidence: 99%
“…Tβ4 was initially employed as an anti-inflammatory agent (Badamchian et al, 2003;Girardi et al, 2003) and, subsequently, to inhibit proliferation and induce differentiation and apoptosis of leukemic cells (Huang et al, 2006). Recently, Tβ4 healing properties were described in skin, cornea and cardiac repair (Zhang et al, 2016a;Chopp and Zhang, 2015;Bock-Marquette et al, 2004;Badamchian et al, 2007;Li et al, 2017;Kim et al, 2017;Goldstein et al, 2012).…”
Section: Thymosins: the Old And The Newmentioning
confidence: 99%
“…The epidermal growth factor receptor and the TLR signal transduction pathways may contribute to CNS remyelination and recovery of function induced by Tβ4 (Zhang et al, 2016a;Santra et al, 2014). Hedgehog signaling pathway was shown to be involved in activation of stem cells after Tβ4 treatment, which may contribute to therapeutic benefit (Kim et al, 2017).…”
Section: The Effects Of Tβ4 On Opc Differentiation and Remyelination mentioning
confidence: 99%